Opioid Usage and Prescribing Predictors Following Transoral Robotic Surgery for Oropharyngeal Cancer. (19th November 2020) - Abt, Nicholas B.; Holcomb, Andrew J.; Feng, Allen L.; Suresh, Krish; Mokhtari, Tara E.; McHugh, Christopher I.; Parikh, Anuraag S.; Faden, Daniel L.; Deschler, Daniel G.; Varvares, Mark A.; Lin, Derrick T.; Richmon, Jeremy D.
Abstract : Objective/Hypothesis: Pain management following transoral robotic surgery (TORS) varies widely. We aim to quantify opioid usage following TORS for oropharyngeal squamous cell carcinoma (OPSCC) and identify prescribing predictors. Study Design: Retrospective cohort study. Methods: A consecutive series of 138 patients undergoing TORS for OPSCC were reviewed from 2016 to 2019. Opioid usage (standardized to morphine milligram equivalents [MME]) was gathered for 12 months post‐surgery via prescribing record cross‐check with the Massachusetts Prescription Awareness Tool. Results: Of 138 OPSCC TORS patients, 92.8% were human papillomavirus (HPV) positive. Adjuvant therapy included radiation (XRT;67.4%) and chemoradiation (cXRT;6.5%). Total MME usage from start of treatment averaged 1395.7 MMEs with 76.4% receiving three prescriptions or less. Categorical analysis showed age <65, male sex, overweight BMI, lower frailty, former smokers, HPV+, higher T stage, and BOT subsite to be associated with increased MMEs. Adjuvant therapy significantly increased MMEs (TORS+XRT:1646.2; TORS+cXRT:2385.0; TORS alone:554.7 [ P  < .001]) and 12‐month opioid prescription totals (TORS+XRT:3.2; TORS+cXRT:5.5; TORS alone:1.6 [ P  < .001]). Adjuvant therapy increased time to taper (total MME in TORS alone versus TORS+XRT/cXRT: 0 to 3 months:428.2 versus 845.5, 4 to 6 months:46.8 versus 541.8, 7 to 9 months:12.4 versus 178.6, 10 to 12 months:11.0 versus 4.4, [ P  < .001]). Positive predictors of opioid prescribing at the 4‐ to 6‐month and 4‐ to 12‐month intervals included adjuvant therapy (odds ratio [OR]:5.56 and 4.51) and mFI‐5 score ≥3 (OR:36.67 and 31.94). Following TORS at 6‐, 9‐, and 12‐month, 15.7%, 6.6%, and 4.1% were still using opioids. Conclusions: In OPSCC treated with TORS, opioid use tapers faster for surgery alone versus with adjuvant therapy. Opioid prescribing risks include adjuvant therapy and higher frailty index. Level of Evidence: 4 Laryngoscope, 131:E1888–E1894, 2021